2022
DOI: 10.1186/s13023-022-02506-3
|View full text |Cite
|
Sign up to set email alerts
|

Recapitulation of pro-inflammatory signature of monocytes with ACVR1A mutation using FOP patient-derived iPSCs

Abstract: Background Fibrodysplasia ossificans progressiva (FOP) is a rare genetic disease characterized by progressive heterotopic ossification (HO) in soft tissues due to a heterozygous mutation of the ACVR1A gene (FOP-ACVR1A), which erroneously transduces the BMP signal by Activin-A. Although inflammation is known to trigger HO in FOP, the role of FOP-ACVR1A on inflammatory cells remains to be elucidated. Results We generated immortalized monocytic cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…When monocytes collected from FOP patients were stimulated with lipopolysaccharide (LPS), they showed the prolonged activation of NF-κB, suggesting its role in FOP inflammation [37]. These and other findings have shown that ACVR1 activity causes a pro-inflammatory state through increased NF-κB [183]. Additionally, transforming growth factor beta (TGF-β), a cytokine released by monocytes and macrophages, is increased in FOP patients and has been shown to attenuate HO formation in FOP mouse models when systemically suppressed [37,118].…”
Section: Inflammatory Control Of Homentioning
confidence: 75%
“…When monocytes collected from FOP patients were stimulated with lipopolysaccharide (LPS), they showed the prolonged activation of NF-κB, suggesting its role in FOP inflammation [37]. These and other findings have shown that ACVR1 activity causes a pro-inflammatory state through increased NF-κB [183]. Additionally, transforming growth factor beta (TGF-β), a cytokine released by monocytes and macrophages, is increased in FOP patients and has been shown to attenuate HO formation in FOP mouse models when systemically suppressed [37,118].…”
Section: Inflammatory Control Of Homentioning
confidence: 75%
“…In order to produce healthy bone-forming cells that can replace the abnormally formed bone, researchers are investigating the use of iPSCs in FOP. This strategy shows potential for regenerating healthy tissue and functionality [45,46]. A number of transcription factors, including Oct4, Sox2, Klf4, and c-Myc, can be added to somatic cells to produce iPSCs.…”
Section: Induced Pluripotent Stem Cells (Ipscs)mentioning
confidence: 99%
“…Researchers are looking into several immunotherapeutic strategies that can specifically target the cells responsible for aberrant bone growth, such as monoclonal antibodies and immune checkpoint inhibitors. These treatments seek to prevent or lessen HO in FOP by regulating the immunological response [9,46]. Monoclonal antibodies are proteins that can attach to particular antigens on the surface of cells and cause the immune system to start destroying those cells.…”
Section: Immunotherapymentioning
confidence: 99%
“…Notable differences were observed in FOP iPSC-derived M1 macrophages, which exhibited higher expression levels of IL6, IL1a, RANTES, and Activin-A, among others. Maekawa et al pursued a different approach by differentiating isogenic iPSC lines into the monocytic lineage and subsequently immortalizing the cells [128,129]. FOP immortalized monocytes (FOP-ML) displayed elevated levels of phosphorylated SMAD5, both at basal levels and upon stimulation with recombinant Activin-A, unlike the control cells.…”
Section: Fibrodysplasia Ossificans Progressiva and Hipscsmentioning
confidence: 99%